2006
DOI: 10.1212/01.wnl.0000194507.39504.17
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol, APOE genotype, and Alzheimer disease

Abstract: Objective-To examine the relationship between cholesterol and other lipids, APOE genotype, and risk of Alzheimer disease (AD) in a population-based study of elderly Yoruba living in Ibadan, Nigeria.Methods-Blood samples and clinical data were collected from Yoruba study participants aged 70 years and older (N = 1,075) as part of the Indianapolis-Ibadan Dementia Project, a longitudinal epidemiologic study of AD. Cholesterol, low-density lipoprotein (LDL), high-density lipoprotein (HDL), and triglyceride levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(95 citation statements)
references
References 41 publications
(41 reference statements)
3
89
0
3
Order By: Relevance
“…12,15,16,[18][19][20][21][22][23] In one paper, two studies were reported, and we considered these studies separately. 24 Because of considerable heterogeneity in methods (sampling and study design), population samples (age, health, socioeconomic status, geographical region and cultural background) and screening or diagnostic measures, we did not pool the data but report our findings in narrative form.…”
Section: Data Extraction and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…12,15,16,[18][19][20][21][22][23] In one paper, two studies were reported, and we considered these studies separately. 24 Because of considerable heterogeneity in methods (sampling and study design), population samples (age, health, socioeconomic status, geographical region and cultural background) and screening or diagnostic measures, we did not pool the data but report our findings in narrative form.…”
Section: Data Extraction and Analysismentioning
confidence: 99%
“…Only three studies documented evidence that confirmed the reliability of the tools. 12,15,16,[18][19][20][21][22][23]30,32 Three studies did not report confidence intervals (or information necessary to calculate them) 27,29,32 and one did not report a confidence interval but provided enough information for this to be calculated. 33 One study did not document sufficient information regarding appropriate probability sampling.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Boyle's discussion also lends credence to the ability to prevent AD and its progression or severity through lifestyle modifications, contradicting Wadman's [12] statement that preventive measures are unknown. Normal aging processes do not lead to inevitable dementia.…”
Section: Resultsmentioning
confidence: 94%
“…This trial also will investigate whether a low dose of pioglitazone (already approved at much higher doses for type 2 diabetes treatment) can delay disease onset in those individuals deemed to be at high risk of AD. Evidence from animal and small scale human studies suggest that pioglitazone may prevent or reverse AD-related pathology and symptoms [12]. As technology advances and knowledge expands related to the initiative, as well as study investment by these researchers and the junction of forces and funding of visionary pharmaceutical companies, new and potentially better resources and treatments will be on the horizon to sustain and prolong the patients' quality of life.…”
Section: Researchmentioning
confidence: 99%
“…One study found the risk was reduced for people with a high level of cholesterol [67]. There is some evidence to suggest that high cholesterol levels may have variable impacts in different ethnic groups [68].…”
Section: Comorbiditiesmentioning
confidence: 99%